Revisions of two poorly known species of Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) with description of a new species from China - Wang, Ying-Yong; Guo, Qiang; Liu, Zu-Yao; Lyu, Zhi-Tong; Wang, Jian; Luo, Lin; Sun, Yan-Jun; Zhang, Yan-Wu (Zootaxa, 2017)
The previous descriptions of Opisthotropis maxwelli Boulenger, 1914 and O. andersonii (Boulenger, 1888) were considered imperfect due to the limited number of specimens. This may in turn cause a problem for accurate species identification. In our study, the species boundaries of these two species were investigated using an integrative approach incorporating morphological characters and molecular phylogenetic analyses of the mitochondrial Cyt b gene of 26 specimens of nine known Opisthotropis species collected from south-eastern China. Our results surprisingly revealed a new cryptic species, Opisthotropis shenzhenensis sp. nov., from Shenzhen and Dongguan, Guangdong Province, southern China. Further, we re-described O. maxwelli based on several specimens from Fujian and Guangdong, and O. andersonii based on a series of specimens from Hong Kong, Shenzhen and Guangzhou, China. We provide an updated identification key to all described Opisthotropis species from China.